The development of environment based textbook in biology course at Tribhuwana Tunggadewi University - Nugroho Aji Prasetiyo; Pertiwi Perwiraningtyas (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
Environmental issues are rooted in human behavior is often found in everyday life, one contributing factor was not maximal the environment learning outcomes in the education. The purpose of this study is to develop environment based textbook in Biology course suited to the needs and character of college students. The development model used in this research and development are modified Thiagarajan et al model consists of three stages: define, design, and develop. The technique of collecting data using questionnaires validation for experts, and small-scale trials. The result of the development of textbooks showing the average results of the validation and testing is in the category with a good fit for use in accordance with the table eligibility criteria and product revision level.